Human Alveolar Macrophage-derived Chemotactic Factor for Neutrophils: STIMULI AND PARTIAL CHARACTERIZATION - Hunninghake, Gary W. (1980)
The presence of neutrophils within the lung is a characteristic feature of a variety of lung diseases. To evaluate the potential role of alveolar macrophages in modulating the migration of neutrophils to the lung, normal human alveolar macrophages obtained from volunteers by bronchopulmonary lavage, were exposed for various periods of time in vitro to heat-killed microorganisms, and noninfectious particulates, immune complexes, and the macrophage supernates were evaluated for chemotactic activity. The microorganisms, noninfectious particulates, and immune complexes were chosen as stimuli for alveolar macrophages because these stimuli are representative of a spectrum of pathogenic agents that cause neutrophil accumulation in the lower respiratory tract. After incubation with each of these stimuli, alveolar macrophages released low molecular weight (400-600) chemotactic factor(s) (alveolar macrophage-derived chemotactic factor[s] [AMCF]) with relatively more activity for neutrophils than monocytes or eosinophils. Checker-board analysis of the AMCF revealed that the factor was primarily chemotactic and not chemokinetic for neutrophils. The selectivity for neutrophils vs. monocytes could not be explained by a selective deactivation of monocytes, because the AMCF was more potent in deactivating neutrophils than monocytes. Partial characterization of AMCF demonstrated it was heterogeneous with the following features: (a) stable to heating at 56 and 100°C for 30 min; (b) stable over a pH range of 1.0 to 12.0 for 60 min; (c) stable after exposure to trypsin, papain, chymotrypsin, collagenase, and elastase; (d) partially inhibited by serum chemotactic factor inhibitor(s); (e) two major isoelectric points (pI 7.6 and 5.2); and (f) partially extractable into ethyl acetate, ether, and hexane. Although AMCF was, at least, partially lipid in nature, it did not appear to be similar to previously described lipid chemotactic factors (e.g., hydroxy-derivatives of 5,8,10,14-eicosatetraenoic acid); analysis by gas chromatography-mass spectrophotometry of AMCF extracted into ethyl acetate did not reveal the presence of 5,8,10,14-eicosatetraenoic acid. The macrophage supernates containing the AMCF also stimulated normal human neutrophils to release lysozyme and lactoferrin but not lactate dehydrogenase. These studies suggest that a wide variety of potentially pathogenic stimuli induce normal alveolar macrophages to generate a low molecular weight chemotactic factor(s) that preferentially attracts neutrophils. Because alveolar macrophages are normal residents of alveoli, it is likely that by releasing this factor(s) macrophages play a significant role in amplifying the inflammatory processes seen in many acute and chronic lung diseases.